2010
DOI: 10.1136/adc.2010.187617
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study to test the predictability of the Melbourne criteria for activation of the medical emergency team

Abstract: The MAC has a low PPV and its full implementation would result in a large number of false positive triggers. Further research is required to determine the relative contribution of the components of this complex intervention (Paediatric Early Warning System, education and MET) on patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Our previous study found using a snap shot methodology that 42% of all potential RRS activations were in fact not made [10,11]. However, the importance of this is unclear, when the positive and negative predictive value of the various activation criteria, are so low [12][13][14][15]23]. However, from a more practical standpoint, our organisation was principally concerned with the missed/delayed RRS activation that was associated with patient harm to such a degree that either intensive care admission was required or, worse, that a cardiac arrest occurred.…”
Section: Study Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous study found using a snap shot methodology that 42% of all potential RRS activations were in fact not made [10,11]. However, the importance of this is unclear, when the positive and negative predictive value of the various activation criteria, are so low [12][13][14][15]23]. However, from a more practical standpoint, our organisation was principally concerned with the missed/delayed RRS activation that was associated with patient harm to such a degree that either intensive care admission was required or, worse, that a cardiac arrest occurred.…”
Section: Study Limitationsmentioning
confidence: 98%
“…Attempts to validate such rules have demonstrated that, on the whole, the activation criteria have reasonable negative predictive value. However, the adherence to rules invariably has a poor positive predictive value generally due to low sensitivity of the criteria [12][13][14][15]. For the clinician faced with using the RRS this translates to a set of rules that mean the RRS must be called, but the net result of that is that there is minimal to no intervention and the patient does just fine sitting there in their ward bed [23].…”
Section: Study Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Most EWS use expert-derived normal ranges for age [9,40,41]. However, recent data suggests that normal distributions for heart and respiratory rate in well and sick hospitalized children are significantly different from published ranges [41, 42•].…”
Section: Normal Abnormal and Normally Abnormal Vital Signsmentioning
confidence: 99%
“…The Cardiff system has undergone a prospective evaluation and also applied the Australian MET system to its own unit 25 26. In both the Cardiff studies, the systems had reasonable sensitivities but at the cost of low specificity and positive predictive value, that is, few critical children were missed but a number of children activated unnecessarily.…”
Section: Development Of Children's Systemsmentioning
confidence: 99%